2020
DOI: 10.1016/j.xfnr.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on the genetic causes of diminished ovarian reserve and opportunities for genetic screening: systematic review and meta-analysis

Abstract: Objective: To provide an update on single-gene mutations identified as causative for pathologic diminished ovarian reserve (DOR) to inform clinical screening recommendations. Evidence Review: A systematic review of the literature was performed in accordance with PRISMA guidelines using PubMed and EM-BASE databases. Only full-text articles in English were included and articles were excluded that did not relate to single-gene causes of pathologic DOR in humans. The search was supplemented using references of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 146 publications
(183 reference statements)
0
6
0
3
Order By: Relevance
“…Genetic factors are among the causes of POR. More specifically a recent meta-analysis reported that mutations in FMR1 , and FMR2 , along with polymorphisms in the BMP-15 , GDF-9 , in the gene encoding the receptor of FSH ( FSHR ) and in the NOBOX gene may present as a cause for POR [ 235 ]. The FMR1 gene is associated with fragile X syndrome in the offspring [ 236 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic factors are among the causes of POR. More specifically a recent meta-analysis reported that mutations in FMR1 , and FMR2 , along with polymorphisms in the BMP-15 , GDF-9 , in the gene encoding the receptor of FSH ( FSHR ) and in the NOBOX gene may present as a cause for POR [ 235 ]. The FMR1 gene is associated with fragile X syndrome in the offspring [ 236 ].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, BMP-15 mRNA levels in embryos have been positively associated with embryo viability. Furthermore, other candidate genes have also been investigated regarding their role in the pathophysiology of POR, including BRCA1 and BRCA2 [ 235 ], IGF-1 , IGF-2 , along with their respective receptors, AMH , LHCGR and GREM1 [ 239 ], however robust conclusions cannot yet be reached.…”
Section: Resultsmentioning
confidence: 99%
“…При неэффективности возможна инициация фармакотерапии, а при наличии показаний -использование методов бариатрической хирургии. В научной литературе имеются данные об улучшении показателей фертильности, в частности АМГ, на фоне низкокалорийной диеты у пациенток с ожирением [35,36]. Аналогичные результаты были получены у пациенток после проведенной бариатрической операции, где исходный уровень АМГ у пациенток без СПКЯ составлял 1,35±0,76 нг/мл, а после вмешательства 6,23±1,47 нг/мл.…”
Section: эффективность снижения массы тела в профилактике неблагоприя...unclassified
“…The understanding of the etiology of DOR is limited, with current evidence suggesting a complex interplay of genetic and environmental factors. Although variants in several genes have been associated with an increased risk for DOR, including FMR1 , FMR2 , AMHR2 , LHCGR , BMP15 , TR53 , GDF9 , FSHR , and NOBOX , the underlying genetic mechanism remains largely unknown [ 9 , 10 ]. And the identification of specific genetic causes for DOR is hindered by the complex inheritance pattern and the lack of large-scale genetic studies.…”
Section: Introductionmentioning
confidence: 99%